Development and parametric study of a new self-centering rotational friction damper. (15th May 2021) - Veismoradi, Sajad; Yousef-beik, Seyed Mohamad Mahdi; Zarnani, Pouyan; Quenneville, Pierre
Highlights: A new Self-Centering Damage-free damper has been developed. The performance of the damper is analytically investigated. The behavior of the Damper is validated by experimental testing. A parametric Study on the design parameters of the damper is conducted. Abstract: Rotational friction (RF) dampers are among the efficient energy-absorbing devices with nearly elasto-plastic behavior and stable hysteresis response. However, the lack of self-centering features might result in undesirable residual displacement for the buildings equipped with RF dampers, not being re-occupiable quickly after severe events. This paper introduces an innovative seismic device named Self-Centering Rotational Friction damper (SC-RF damper) that can provide both energy dissipation as well as self-centering characteristics. The damper is comprised of especially grooved friction plates clamped by high strength bolts or rods using pre-stressed conical disc springs. Similar to RF dampers, the SC-RF dampers provides a remarkable flexibility not only at the connection component design, but also at the structural system performance. In this paper, the principles of force-deflection relationship for the SC-RF damper are analytically and numerically developed and validated through finite element analysis. Then, a sample prototype damper was manufactured and experimentally tested, to further validate the performance of the system. The effect of disk springs performance on the damper is experimentally investigated in detail. To gain a better understanding about damper's performance, the influence of various parameters affecting the damper's performance are analyzed as well. Finally, the damper's capability including its adaptive stiffness and damping is also investigated in principle. The results highlight the capability of the damper to dissipate seismic energy through rotational friction sliding while providing a stable and repeatable self-centering feature with no requirement for post-event maintenance, ready for aftershocks.